The Global Financial Crisis and its Impact on the Chilean Banking System - Chan-Lau, Jorge (IMF Working Papers; Working Paper, 2010)
This paper explores how the global turmoil affected the risk of banks operating in Chile, and provides evidence that could help strengthen work on vulnerability indicators and off-site supervision. The analysis is based on the study of default risk codependence, or CoRisk, between Chilean banks and global financial institutions. The results suggest that the impact of the global financial crisis was limited, inducing at most a one-rating downgrade to banks operating in Chile. The paper concludes by assessing government measures aimed at reducing systemic risk in the domestic banking sector and the recommendations to allocate SWF assets to domestic banks.